Postmarketing safety and effectiveness of recombinant factor IX (nonacog alfa) in Japanese patients with haemophilia B. Issue 4 (6th June 2019) - Fukutake, Katsuyuki; Taki, Masashi; Matsushita, Tadashi; Sakai, Michio; Takata, Ami; Yamaguchi, Hiromi; Karumori, Toshiyuki
Abstract: Introduction: In 2010, nonacog alfa became the first recombinant factor IX (rFIX) available in Japan for patients with haemophilia B. Aim: To determine real‐world safety (adverse events, incidence of inhibitors) and effectiveness of nonacog alfa in Japan. Methods: This multicentre, prospective, observational, postmarketing surveillance study enrolled previously treated and untreated patients (PTPs and PUPs, respectively) who were observed for 1 and 2 years, respectively, after initiating nonacog alfa therapy. Safety and effectiveness were assessed for each treatment type. Annualized bleeding rate (ABR) and incremental recovery of rFIX were also evaluated. Results: Overall, 312 of 314 patients enrolled from 173 sites were eligible for the safety analysis set (PTPs, 281; PUPs, 28; other, 3). Mean age was 25.4 (PTPs) and 14.8 (PUPs) years. Haemophilic severity ranged from mild to severe, and 133 (42.6%) patients had haemophilic arthropathy. Of 285 patients (PTPs, 257; PUPs, 28) in the effectiveness set, 112 received on‐demand treatment for 1161 bleeding episodes (effectiveness rate, 93.7%) and 185 received routine prophylaxis (effectiveness rate, 95.5%). No spontaneous bleeding was observed in 52.4% of patients during prophylactic treatment. Median ABR was lower during routine prophylaxis (2.0) vs the rest of the observation period (8.3). A weak negative correlation was found between body weight and the reciprocal of rFIX recovery. Eleven adverse drug reactions occurred in 7 PTPs (2.2% [7/312]); recurrence of inhibitor was observed in 1 patient, but no new inhibitor developed in PTPs or PUPs. Conclusion: Nonacog alfa therapy is safe and effective in the real‐world scenario in Japan.